2017
DOI: 10.1002/cncr.30491
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive T cell therapy: An overview of obstacles and opportunities

Abstract: The therapeutic potential of adoptive cell therapy (ACT) in cancer patients was first acknowledged 3 decades ago, but it was an esoteric approach at the time. In recent years, technological advancements have transformed ACT into a viable therapeutic option that can be curative in some patients. In fact, current ACT response rates are 80% to 90% for hematological malignancies and 30% for metastatic melanoma refractory to multiple lines of therapy. Although these results are encouraging, there is still much to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 94 publications
0
71
0
Order By: Relevance
“…The furthest‐developed one in clinic is called a chimeric antigen receptor (CAR). After such a selection, these cells are stimulated to expand in vitro and finally reinfused back to the cancer patient . However, the immune response induced by this approach is limited due to a large amount of ex vivo proliferation (up to 10 11 T cells) and immunosuppressive tumor microenvironment …”
Section: Developing Novel Nanoplatforms For Stimulating Cellular Immumentioning
confidence: 99%
See 1 more Smart Citation
“…The furthest‐developed one in clinic is called a chimeric antigen receptor (CAR). After such a selection, these cells are stimulated to expand in vitro and finally reinfused back to the cancer patient . However, the immune response induced by this approach is limited due to a large amount of ex vivo proliferation (up to 10 11 T cells) and immunosuppressive tumor microenvironment …”
Section: Developing Novel Nanoplatforms For Stimulating Cellular Immumentioning
confidence: 99%
“…After such a selection, these cells are stimulated to expand in vitro and finally reinfused back to the cancer patient. [208] However, the immune response induced by this approach is limited due to a large amount of ex vivo proliferation (up to 10 11 T cells) and immunosuppressive tumor microenvironment. [209] To rapidly expand effector cells into the required quantity, iron-dextran-derived nano-aAPCs were used to selectively bind to tumor specific T cells from the naïve precursors through magnetic force, followed by the elution and extensive culture of positive fractions.…”
Section: Adoptive T Cell Cancer Therapy Enhanced By Nanoparticle-thermentioning
confidence: 99%
“…Additional alternative strategies in cancer immunotherapy include vaccines or cellular therapies, for example, with tumour-infiltrating lymphocytes (TIL) 19 or autologous T cells genetically modified to express chimeric antigen receptors (CAR T cells). 20 BC was initially considered as a non-immunogenic tumour, but recent studies have demonstrated that the expression of immune-related genes and the presence of immune infiltrates in primary tumours were associated with a better clinical outcome, [21][22][23][24][25][26][27] particularly in the most aggressive subtypes (HER2-positive and triple-negative (TNBC)). In addition, and consistent with their function, specific subsets of immune cells were correlated with outcome in BC.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the combined immunotherapy setting with PD-1 blockade and CD137 agonism, AT-3 tumors were not eliminated, despite a robust CTL response. This problem is also evident in cancer patients that fail to respond to adoptive tumor-specific T-cell therapy (Baruch et al, 2017), highlighting that T-cell suppression in the TME can pose an additional bottleneck for systemic anti-tumor immunity. Importantly, our study demonstrates that radiotherapy can alter the state of the TME to permit effective CTL activity, where PD-1 blockade cannot.…”
Section: Discussionmentioning
confidence: 99%